Can Abdominal Computed Tomography Imaging Help Accurately Identify a Dedifferentiated Component in a Well-Differentiated Liposarcoma?. Issue 6 (November 2016) - Bhosale, Priya; Wang, Jieqi; Varma, Datla; Jensen, Corey; Patnana, Madhavi; Wei, Wei; Chauhan, Anil; Feig, Barry; Patel, Shreyaskumar; Somaiah, Neeta; Sagebiel, Tara
Abstract : Purpose: To assess the ability of computed tomography (CT) to differentiate an atypical lipomatous tumor/well-differentiated liposarcoma (WDLPS) from a WDLPS with a dedifferentiated component (DDLPS) within it. Materials and Methods: Forty-nine untreated patients with abdominal atypical lipomatous tumors/well-differentiated liposarcomas who had undergone contrast-enhanced CT were identified using an institutional database. Three radiologists who were blinded to the pathology findings evaluated all the images independently to determine whether a dedifferentiated component was present within the WDLPS. The CT images were evaluated for fat content (⩽25% or >25%); presence of ground-glass density, enhancing and/or necrotic nodules; presence of a capsule surrounding the mass; septations; and presence and pattern of calcifications. A multivariate logistic regression model with generalized estimating equations was used to correlate imaging features with pathology findings. Kappa statistics were calculated to assess agreement between the three radiologists. Results: On the basis of pathological findings, 12 patients had been diagnosed with DDLPS within a WDLPS and 37 had been diagnosed with WDLPS. The presence of an enhancing or a centrally necrotic nodule within the atypical lipomatous tumor was associated with dedifferentiated liposarcoma ( P = 0.02 and P = 0.0003, respectively). The three readers showed almost perfect agreement in overall diagnosis (κ r = 0.83; 95% confidence interval, 0.67–0.99). Conclusions: An enhancing or centrally necrotic nodule may be indicative of a dedifferentiated component in well-differentiated liposarcoma. Ground-glass density nodules may not be indicative of dedifferentiation.